2010
DOI: 10.1021/jf100786h
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Peroxidase from Horseradish (Armoracia rusticana) Roots

Abstract: Peroxidase (EC 1.11.1.7) from horseradish ( Armoracia rusticana ) roots was purified using a simple, rapid, three-step procedure: ultrasonication, ammonium sulfate salt precipitation, and hydrophobic interaction chromatography on phenyl Sepharose CL-4B. The preparation gave an overall yield of 71%, 291-fold purification, and a high specific activity of 772 U mg(-1) protein. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis revealed that the purified enzyme was homogeneous and had a molecular weight of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 33 publications
1
62
2
Order By: Relevance
“…AuNPs were synthesized according to the reported method with slight modifications [7]. All glassware used in the preparation procedure were bathed in freshly prepared aqua regia (1:3 (v/v) HNO 3 -HCl), thoroughly rinsed with doubledeionized water, and dried in an oven prior to use.…”
Section: Preparation Of Aunps and Aunps-anti-igg Conjugatementioning
confidence: 99%
See 1 more Smart Citation
“…AuNPs were synthesized according to the reported method with slight modifications [7]. All glassware used in the preparation procedure were bathed in freshly prepared aqua regia (1:3 (v/v) HNO 3 -HCl), thoroughly rinsed with doubledeionized water, and dried in an oven prior to use.…”
Section: Preparation Of Aunps and Aunps-anti-igg Conjugatementioning
confidence: 99%
“…For example, horseradish peroxidase (HRP) is one of most common enzymes used in the ELISA since it serves as a catalyst to facilitate a series of biological processes [4,5]. However, natural enzyme-labeled systems have some inevitable shortcomings, such as easy denaturation and digestion by proteases, and complicated preparation, purification, and storage processes, which severely limit their routine use in diagnosis [6,7]. Hence, it is necessary to synthesize new non-natural enzymes with high catalytic activity to overcome the restrictions of natural enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The class III plant peroxidases have been reported to play crucial roles in the plant life cycle [13] such as cell wall metabolism [9], lignification [10], suberization [11], auxins metabolism [12], wound healing, reactive oxygen species (ROS) and reactive nitrogen species (RNS) metabolism [13,14], fruit growth and ripening [15], defense against pathogens [16] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Lavery et al (2010) reported the purification of a peroxidase from horseradish roots (Armoracia rusticana) by means of a three-step strategy, consisting of ultrasonication, ammonium sulfate precipitation, and HIC (using Phenyl Sepharose). In this strategy, the only high-resolution purification step corresponded to HIC.…”
mentioning
confidence: 99%